USING CLUSTERING TECHNIQUE TO IMPROVE STUDENTS’ DESCRIPTIVE TEXT WRITING ACHIEVEMENT - Pertiwi, Dian Pertiwi (Faculty of Teaching and Education, University of August 17, 1945, Banyuwangi, 2024)
Writing is a productive skill in learning language. Many students have difficulties in writing a foreign language. Writing needs a long term process and pre activities before paragraph making. This research has a goal to solve the problem above through clustering technique to improve students’ writing achievement in descriptive text. CAR (classroom action research) was chosen as method in this research at Islamic senior high school based in Banyuwangi, East Java, Indonesia. The data of the study was obtained by writing test and observation checklist. All collected data were analyzed quantitatively. The result of writing test shows that there is significant improvement from the score before the action was given. There were 69% out of 26 students achieved minimum passing grade. There was significant improvement from 19% to 69%. The improvement in this study indicates that students are able to produce new ideas into a good text and brainstorm idea before they write a draft. Moreover, the use of clustering technique also could improve students’ active participation the teaching and learning process. The result of students participation increased from 16 students (62%) to 24 students (92%).